Assessment of Dispensing Malpractice in Community Drug Retail Outlets in South Gondar Zone, Northwest Ethiopia: A Simulated Patient Experience - Bogale Kassie A; Mengie Ayele T; Mekonnen Agidew M (Dove Medical Press, 2023)
Achenef Bogale Kassie,1 Teklie Mengie Ayele,1 Melaku Mekonnen Agidew2 1Department of Pharmacy, College of Health Sciences, Debre Tabore University, Debre Tabore, Amhara Regional State, Ethiopia; 2Department of Biomedical Science, College of Health Sciences, Debre Tabore University, Debre Tabore, Amhara Regional State, EthiopiaCorrespondence: Achenef Bogale Kassie, Email kassiebogale@gmail.comBackground: Pharmacy professionals in community drug retail outlets, as the most accessible personnel for the community, are engaged in consultation and responding to health problems in addition to filling prescriptions. In doing so, different dispensing malpractices are observed and much is not known on the issue in Ethiopia.Objective: The study aimed at assessing dispensing malpractice at pharmacies, drug stores and drug vendors in South Gondar zone.Methodology: A cross-sectional study design with a descriptive approach was applied from April 1 to June 30. The data was collected using the simulated patient method. Seven prescription-only medicines and a diarrheal case were requested during visit. All drug retail outlets in South Gondar zone that were in service during data collection were visited.Results: Almost all prescription-only medications were dispensed without prescription at all community drug retail outlets. Of all the dispensaries, 19 (82.6%) provided a partial dosage regimen of amoxicillin. Presence of fever and pregnancy status were asked about by dispensers in only 8% and 20% of visits for diarrhea, respectively. Medication history was also rarely requested. Medication was dispensed in 80% of visits for diarrhea, all of which included antimicrobials. Oral rehydration salt was considered in only two (10%) dispensaries.Conclusion: Dispensing medications without a prescription is common in community drug retail outlets in South Gondar zone in Amhara Regional State. Our findings also showed that detailed assessments of patients' signs and symptoms are not performed properly by the dispensers to understand the diarrheal case. Training of pharmacy professionals and strict regulatory control are needed.Keywords: dispensing malpractice, simulated patient survey, community drug retail outlets